Tattoos, piercings, and symptoms of ADHD in non-clinical adults: a cross-sectional study - Glans, Martin Ragnar; Nilsson, Joel; Bejerot, Susanne (Frontiers in Psychiatry, 2024)
Introduction Tattoos and piercings are associated with impulsive and risk-taking personality traits, which are also common along the ADHD continuum. However, studies on ADHD and body modification are lacking. Thus, this study aimed to assess the association between body modification and subclinical ADHD symptom severity and to investigate if body modification can serve as an indication for ADHD examination. Methods A total of 762 adults (529 women and 233 men) without a diagnosis of ADHD completed the adult ADHD Self-Report Scale (ASRS) and answered questions concerning body modification. Two different ASRS versions were utilized: the 18-item ASRS Symptom Checklist and the 6-item ASRS Screener. Three categorizations of body modifications were analyzed: (i) having at least one tattoo, (ii) having at least one piercing other than ear piercing, and (iii) the combination of simultaneously having at least one tattoo and one piercing. Mean 18-item ASRS total and subscale scores and the proportion of positive results on the 6-item ASRS Screener were compared between those with and those without body modifications while adjusting for covariates age and sex. Additional analyses were performed for ≥2 and ≥3 body modifications. Results In our cohort, 26% had a tattoo, 14% had a piercing other than ear piercing, and 8% had a combination of tattoo and piercing. Having any kind of body modification was associated with more pronounced symptoms of ADHD and with a cutoff score on the ASRS screener indicating ADHD. Whereas, the effect sizes were small for tattoos, medium to large effect sizes were seen for ≥2 piercings in the ASRS. Moreover, moderately strong associations emerged for ≥1 piercing and a positive ASRS screening result. Conclusion Our results suggest that acquiring a body modification, especially a tattoo, is entering the mainstream in Sweden. Correspondingly, differences in subclinical ADHD symptomatology between non-clinical adults with and without body modifications are subtle. Having ≥2 piercings other than ear piercings, on the other hand, is associated with clinically relevant differences in ADHD symptoms. Moreover, piercing status may serve as an indicator, among others, for further ADHD assessments. However, more research is needed to ascertain the possible signaling functions of body modifications in clinical settings.